SPONTANEOUS FECAL FISTULA: A RARE PRESENTATION OF INGUINAL HERNIA - Samad, Abdul; Sheikh, Gul Muhammad (Journal of Ayub Medical College Abbottabad, 2005)
A 25 years old young man presented with the right scrotal and supra-pubic fecal fistulae due to the spontaneous bursting of a congenital inguinal hernia. This hernia remained obstructed and strangulated for about ten days before getting ruptured. Resection and end to end anastomosis of involved ileum was done. The literature search could reveal only five such cases in pediatric age group and this complication is considered to be much rarer among the adult population. This case report is being presented here in view of the extreme rarity of this complication in the adult age group. Keywords: Inguinal hernia, Congenital, Spontaneous, Fecal fistula, Incarcerated hernia